Optimization of p-chart for Processes with Multiple Assignable Causes and Random Shift - Mohammed, Emad Aldin Mohammed Abdelkreem (2020)
A Master of Science thesis in Engineering Systems Management by Emad Aldin Mohammed Abdelkreem Mohammed entitled, “Optimization of P-Chart for Processes with Multiple Assignable Causes and Random Shift”, submitted in May 2020. Thesis advisor is Dr. Mahmoud Awad. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).